Auditoría de gestión al departamento de talento humano y su incidencia en la toma de decisiones de la hacienda Tabaganesha S.A., cantón Buena Fe, año 2013 - Fuentes Fuentes, Deisy Viviana (2015)
The main objective of the research project is to conduct a management audit Human Resource department and its impact on decision-making of the estate Tabaganesha SA, Canton Good Faith, 2013. which was developed by applying the hypothetical method -Deductivo, analytical, inductive, also investigative techniques such as the observation of internal control questionnaire by applying the COSO II to the coordinator of human talent to research more efficient and thus detect deficiencies in that area and giving the respective recommendations for the proper operation thereof, interviews the Manager and the Administrator and surveys of the farm workers, the types of research that the field was applied, descriptive and bibliographic and finally design research. The findings indicate that certain identified the hacienda Tabaganesha SA has deficiencies in policies and standards set with a percentage of 21% (low); breach of the duties incumbent on the Department of Human Both 33% (under moderate) and compliance with the objectives and plans scheduled in the department of human talent is 67% (moderately high), this is due to the absence of a program of recruitment and hence poor staff performance, causing the failure of the assigned duties; this does not help comply fully with the goals set in the property, due to inadequate planning in the Department of Human Resource. After meeting the research findings in the report Internal Control detailing each of the findings and finally the Management Audit report detailing management indicators used in the study was written.